PENDAMPINGAN MENSTRUASI ISLAMI MELALUI KULTUM BAGI SISWI SMP FILOSOFI ISLAMIC BOARDING SCHOOL - Nor Fadhila Herniyanti; Miranda Miranda (JIP: Jurnal Ilmu Pendidikan, 2025)
Menstruation is a natural biological process that is often still considered taboo among adolescent girls, especially in religious-based educational environments. Lack of literacy about menstruation has an impact on psychological unpreparedness and misunderstanding regarding health and worship aspects. This study aims to assess the effectiveness of kultum (seven-minute lectures) as a medium for Islamic menstruation counselling for female students in a boarding school. The method used is an educational-spiritual approach through thematic kultum that discusses menstruation from the perspectives of fiqh, etiquette, hygiene, and self-acceptance. The evaluation results showed a significant increase in understanding, positive attitudes, and openness among female students toward menstruation issues. Supporting factors include school support, student enthusiasm, and boarding school culture, while challenges stem from time constraints and psychological factors. This guidance programme demonstrates that kultum can serve as an innovative approach to effectively and practically integrate health education and Islamic values.